Pengaruh Rasio Profitabilitas dan Rasio Leverage Terhadap Harga Saham pada Perusahaan Telekomunikasi yang Terdaftar di Bursa Efek Indonesia Periode 2018-2021 - Ardzyka Raka Ramadhan; Heikal Muhammad Zakaria (Peneliti.net, 2023)
This research aims to determine the effect of profitability and leverage ratios on stock prices in telecommunications sub-sector companies in 2018-2021. The population in this study was 19 telecommunication companies listed on the Indonesia Stock Exchange from 2018 to 2021. The sample in this study was selected using a purposive sampling technique so that 16 companies were determined that meet the research criteria. This study's analytical methods include multiple linear regression analysis, classical assumption testing, and hypothesis testing. The results showed that Return on Equity (ROE) did not affect stock prices, Debt Equity Ratio (DER) did not affect stock prices, and Return on Equity (ROE) and Debt Equity Ratio (DER) had no effect on stock prices simultaneously.